Elmer - Alanguilan, Gerry ([Laguna] : Komikero Publishing, 2011)
Jake Gallo, an intelligent chicken, returns to the farm where his father, Elmer, one of the first sentient chickens, is dying, where he reads Elmer's diary and talks to the man who protected his parents before chickens were declared human.
"For mature readers."--Cover.
Winner, Best Asian Album, Japan Expo Awards 2011
Nominee, Best New Graphic Album, 2011
Nominee, Will Eisner Comic Industry Awards, Comic-Con International
Keywords: Chickens -- Comic books, strips, etc; Racism -- Comic books, strips, etc